Draft Annual Plan 1984-85 Volume II Government of Uttar Pradesh, Planning Department - Planning Commission (Planning Commission, 1983)
Summary Statement of Outlays and Expenditure , Scheme-wise Outlays and Expenditure , Targets of Production and Physical Achievements , Minimum Needs Programme — Summary of Outlays and Expenditure , Minimum Needs Programme — Scheme-wise details of Outlays and Expenditure , Minimum Needs Programme — Targets and Physical Achievements , Summary of Centrally Sponsored Schemes , Scheme-wise details of Centrally Sponsored Schemes , 20 Point Programme — Outlays and Expenditure , 20 Point Programme — Targets and Achievements
Draft Annual Plan 1984-85 Volume II
Government of Uttar Pradesh